Implementation of ECDSA and MLDSA Digital Signature Schemes for Transaction Authentication on Blockchain - Ridwan Muhammad Raihan; Alam Rahmatulloh (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2026)
Blockchain technology serves as a core foundation for decentralized systems that demand high levels of security, transparency, and data integrity. However, the advancement of quantum computing introduces substantial risks to classical cryptographic algorithms such as the Elliptic Curve Digital Signature Algorithm (ECDSA), which is vulnerable to attacks targeting the discrete logarithm problem. This study proposes a hybrid digital signature scheme that integrates ECDSA with the Module Lattice-based Digital Signature Algorithm (MLDSA) to strengthen blockchain transaction authentication against both classical and quantum threats. Experimental results shown that the hybrid scheme achieves efficient performance, with an average verification time of 0.647 ms and a signing time of 0.806 ms. Although the resulting signature size reaches 6761 bytes due to the concatenation of two signatures, the hybrid approach successfully provides dual-layered cryptographic protection capable of maintaining transaction authenticity and integrity in a post-quantum environment. These findings highlight the feasibility of adopting hybrid digital signatures in blockchain systems. Future work may focus on optimizing signature size through compression techniques to improve scalability and reduce payload overhead.